MicroRNAs as key regulators of GTPase-mediated apical actin reorganization in multiciliated epithelia. (2nd April 2016) - Mercey, Olivier; Kodjabachian, Laurent; Barbry, Pascal; Marcet, Brice
ABSTRACT: Multiciliated cells (MCCs), which are present in specialized vertebrate tissues such as mucociliary epithelia, project hundreds of motile cilia from their apical membrane. Coordinated ciliary beating in MCCs contributes to fluid propulsion in several biological processes. In a previous work, we demonstrated that microRNAs of the miR-34/449 family act as new conserved regulators of MCC differentiation by specifically repressing cell cycle genes and the Notch pathway. Recently, we have shown that miR-34/449 also modulate small GTPase pathways to promote, in a later stage of differentiation, the assembly of the apical actin network, a prerequisite for proper anchoring of centrioles-derived neo-synthesized basal bodies. We characterized several miR-34/449 targets related to small GTPase pathways including R-Ras, which represents a key and conserved regulator during MCC differentiation. Direct RRAS repression by miR-34/449 is necessary for apical actin meshwork assembly, notably by allowing the apical relocalization of the actin binding protein Filamin-A near basal bodies. Our studies establish miR-34/449 as central players that orchestrate several steps of MCC differentiation program by regulating distinct signaling pathways.